Interrelations in multi-source geohazard monitoring for safety management of infrastructure systems. Issue 3 (3rd March 2016) - Sigtryggsdóttir, Fjóla G.; Snæbjörnsson, Jónas Thór; Grande, Lars; Sigbjörnsson, Ragnar
Abstract : In this paper a methodology is put forward for enhancing safety by linking multi-source monitoring to multi-hazards threatening infrastructure systems. An application is demonstrated with a conceptual model comprising two systems. One system includes the infrastructure, exemplified by a reservoir and its dams, along with settings for geohazards. The other system contains the associated monitoring possibilities. Interrelations are quantitatively explored by applying an existing method of systems theory, extended to include multiple systems. This is used to investigate geohazard-triggering potential, interaction intensity and dominance. It is further used to explore the reaction of monitoring components to geohazard action as well as safety values of the monitoring system and its components. The interrelations established have a general relevance for the consideration of geohazards threatening reservoirs and dams, and the associated monitoring. This is explained with a case study. Moreover, the interrelations can be used for defining hazard chains in multi-hazard assessment, planning of monitoring programmes and detecting precursory pathways within a monitoring system. The methodology constitutes the basis for comprehensive safety and risk management embracing, multi-hazard assessment as well as structural health monitoring.